USP15 regulates radiation-induced DNA damage and intestinal injury through K48-linked deubiquitination and stabilisation of ATM - Ruiqiu Zhu; Mingyue Li; Difan Wang; Chengzhi Liu; Liwei Xie; Yinyin Yang; Xuhao Gu; Kui Zhao; Ye Tian; Shang Cai (Molecular Medicine)
Abstract Background Radiation-induced intestinal injury (RIII) interrupts the scheduled processes of abdominal and pelvic radiotherapy (RT) and compromises the quality of life of cancer survivors. However, the specific regulators and mechanisms underlying the effects of RIII remain unknown. The biological effects of RT are caused primarily by DNA damage, and ataxia telangiectasia mutated (ATM) is a core protein of the DNA damage response (DDR). However, whether ATM is regulated by deubiquitination signaling remains unclear. Methods We established animal and cellular models of RIII. The effects of ubiquitin-specific protease 15 (USP15) on DNA damage and radion-induced intestinal injury were evaluated. Mass spectrometry analysis, truncation tests, and immunoprecipitation were used to identify USP15 as a binding partner of ATM and to investigate the ubiquitination of ATM. Finally, the relationship between the USP15/ATM axes was further determined via subsequent experiments. Results In this study, we identified the deubiquitylating enzyme USP15 as a regulator of DNA damage and the pathological progression of RIII. Irradiation upregulates the expression of USP15, whereas pharmacological inhibition of USP15 exacerbates radiation-induced DNA damage and RIII both in vivo and in vitro. Mechanistically, USP15 interacts with, deubiquitinates, and stabilises ATM via K48-linked deubiquitination. Notably, ATM overexpression blocks the effect of USP15 genetic inhibition on DNA damage and RIII progression. Conclusions These findings describe ATM as a novel deubiquitination target of USP15 upon radiation-induced DNA damage and intestinal injury, and provides experimental support for USP15/ATM axis as a potential target for developing strategies that mitigate RIII.